2014
DOI: 10.4314/sajas.v43i5.4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary lipid saturation and antioxidant source on the nutrient digestibility of lamb finishing diets

Abstract: ________________________________________________________________________________ AbstractThe influence of a synthetic or natural antioxidant and lipid saturation on the apparent digestibility of nutrients in a standard lamb finishing diet was investigated. The four dietary treatments consisted of the same basal diet, providing 187 g CP-, 355 g NDF-and 71 g EE per kg DM, but differing in supplemental lipid source (30 g/kg of either saturated beef tallow or unsaturated soybean oil) and type of antioxidant includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In agreement with the current results, previous studies using grain-based diets and BT at 40 g/kg DM have shown that the added fat did not affect growth performance and ruminal fermentation in finishing beef cattle (Guerrero et al, 2016;Lopez et al, 2016). Moreover, in finishing lambs, saturated beef tallow (30 g/kg DM) has been shown not to affect DMI (Booyens et al, 2013). Steers fed diets based on steam-flaked corn and supplemented with 0 and 40 g BT/kg DM also had similar rumen pH values, VFA molar proportion and ammonia N concentrations (Montgomery et al, 2008).…”
Section: Resultssupporting
confidence: 92%
“…In agreement with the current results, previous studies using grain-based diets and BT at 40 g/kg DM have shown that the added fat did not affect growth performance and ruminal fermentation in finishing beef cattle (Guerrero et al, 2016;Lopez et al, 2016). Moreover, in finishing lambs, saturated beef tallow (30 g/kg DM) has been shown not to affect DMI (Booyens et al, 2013). Steers fed diets based on steam-flaked corn and supplemented with 0 and 40 g BT/kg DM also had similar rumen pH values, VFA molar proportion and ammonia N concentrations (Montgomery et al, 2008).…”
Section: Resultssupporting
confidence: 92%
“…From the results (Table 1) it would seem that lipid saturation and antioxidant type had no-significant (P >0.05) influence on the dry matter intake (DMI) of the lambs. This was expected due to the similar dietary nutrient composition, especially NDF content (Booyens et al, 2013). It was evident that a lipid x antioxidant interaction (P <0.05) occurred for the metabolizable energy intake (MEI) of lambs.…”
Section: Resultsmentioning
confidence: 77%
“…As the inclusion of an unsaturated lipid source has a negative effect on fibre digestibility due to its antimicrobial (Palmquist & Jenkins, 1980) and coating (Firkins & Eastridge, 1994;Harris, 2003) effect, it could result in less energy being lost as heat in the rumen -resulting in more energy being available for productive purposes by the animal. The reduced production of ruminal CH 4 within the unsaturated treatment, as reported by Booyens et al (2013), could also contribute to the nonsignificant differences recorded. Therefore, both the heat increment of fermentation, as well as CH 4 production was probably reduced by the unsaturated lipid source, resulting in the non-significant differences.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations